2022
DOI: 10.1097/sih.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Are Video Recordings Reliable for Assessing Surgical Performance? A Prospective Reliability Study Using Generalizability Theory

Abstract: Introduction: Reliability is pivotal in surgical skills assessment. Video-based assessment can be used for objective assessment without physical presence of assessors. However, its reliability for surgical assessments remains largely unexplored. In this study, we evaluated the reliability of video-based versus physical assessments of novices' surgical performances on human cadavers and 3D-printed models-an emerging simulation modality. Methods: Eighteen otorhinolaryngology residents performed 2 to 3 mastoidect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Decision (D) studies revealed that two raters rating one performance or one rater rating two performances would be sufficient for reliable, high-stakes assessment. This is valuable as final-product assessment is time consuming, and even though reliability of video-based assessments is comparable to physical ratings (41), assessment is still rater dependent. In contrast, VR simulation offers automated assessment and feedback based on real-time simulator metrics, enabling instant feedback independently of senior colleagues' feedback (38,(42)(43)(44).…”
Section: D-printed Models For Temporal Bone Training E501mentioning
confidence: 99%
“…Decision (D) studies revealed that two raters rating one performance or one rater rating two performances would be sufficient for reliable, high-stakes assessment. This is valuable as final-product assessment is time consuming, and even though reliability of video-based assessments is comparable to physical ratings (41), assessment is still rater dependent. In contrast, VR simulation offers automated assessment and feedback based on real-time simulator metrics, enabling instant feedback independently of senior colleagues' feedback (38,(42)(43)(44).…”
Section: D-printed Models For Temporal Bone Training E501mentioning
confidence: 99%